Cleavage politics, polarisation and participation in Western Europe - Endre Borbáth; Swen Hutter; Arndt Leininger (West European Politics, 2023)
Polarisation over cultural issues and the emergence of radical, often populist, challenger parties indicate a fundamental restructuring of political conflict in Western Europe. The emerging divide crosscuts and, in part, reshapes older cleavages. This special issue introduction highlights how the transformation of cleavage structures relates to the dynamics of polarisation and political participation. The contributions to the special issue innovate in two ways. First, they adapt concepts and measures of ideological and affective polarisation to the context of Europe's multi-party and multi-dimensional party competition. Second, they emphasise electoral and protest politics, examining how ideological and affective polarisation shape electoral and non-electoral participation. Apart from introducing the contributions, the introduction combines different datasets – the Chapel Hill Expert Survey, Comparative Study of Electoral Systems and the European Social Survey – to sketch an empirical picture of differentiated polarisation with types of polarisation only weakly associated cross-arena, cross-nationally and over time.
Keywords: 320; Ideological polarisation; affective polarisation; political participation; cleavages; protest